The British Asian Muslim male sport participation puzzle: an exploration of implications for sport development policy and practice. (14th September 2017) - Mackintosh, C.; Dempsey, C.
ABSTRACT: The purpose of this study is to explore intersections between religion, faith and social identity with regards to their impact on either promoting or preventing sport participation amongst self-identified British Asian Muslim males living in Birmingham (West Midlands of the UK) aged 16–25 years old. The research questions around this topic of study are to explore how interpretations of Islamic faith promote or prevent sport participation amongst young Muslim males. Secondly, the paper will examine the perspectives of Muslim male participants in relation to sport to identify factors determining sport participation. Finally, the study will consider implications for policy and practice in sport development. The study drew upon seven in-depth, semi-structured interviews with Muslim males aged 16–25 years old and applied a thematic analysis and coding methodology to unpick the key dimensions and findings from the data. Findings from the study indicate the complexity of young Muslim male sport participation contexts, dynamics in decision-making, family influence and perceptions held about other communities and their own. The study draws out key implications for agencies in sport development that seek to encourage sport participation cutting across school, community, local government and national governing body partnerships specifically considering Islamic faith communities.